UDP Pervasive Protocol Integration with IoT for Smart Home Environment using LabVIEW - Mochammad Hannats Hanafi Ichsan; Wijaya Kurniawan; Sabriansyah Rizqika Akbar (Institute of Advanced Engineering and Science, 2018)
Pervasive computing is an environment which is used and integrated into every object and activities to meet human needs and its existence isn’t perceived as something specific. The concept of Smart Home is to assist human needs in an everyday object that performs controls or being controlled. Based on previous research the used communication protocol is UDP (User Datagram Protocol) and the programming language is LabVIEW. UDP is used because it does not require handshaking in the broadcast process, as well as on the use of memory more efficient than other protocols. Devices which perform controls called Host and which is controlled called Client. Both of them (Things) have an ability to send data to the Internet without any human interaction. So this research wants to conduct pervasive protocol between Host and Client which each device is integrated with the Internet of Things (IoT). Data are posted at dweet.io that is a cloud server website that contains a simple online data submission which has free services. This research is conducted to measure the communication performance between host to client, host to cloud server and client to cloud server that represents household equipment.